IMPROVING STUDENTS’ ABILITY IN WRITING NARRATIVE TEXT BY USING PICTURE SERIES (ELang | An English Language Education Journal, 2023)
The title of the research paper was “Improving Students’ Ability in Writing Narrative Text by Using Picture Series”. This study was conducted on the 25th of July 2022 until 29th of July 2022. The objectives of the study were to find out whether or not the picture series were effectively used for improving students' ability in writing narrative text and to find out what were the students' responses toward the use of picture series. The method that was used in this research was pre-experimental design. There was only one group to be researched. The sample was the tenth grade students of SMA AL QONA’AH that consisted of 20 students. The instruments were a test and questionnaire. The research findings were the value of t- test was higher than the t-table (4.322 > 2.093) so that the Null Hypotheses (Ho) is rejected and the Alternative Hypotheses (Ha) is accepted. Stating that there was significant difference in the result of students' score before and after the treatment using picture series. This means that the use of picture series in improving students' ability in writing narrative text to the tenth grade of SMA AL QONA’AH is effective. Then the researcher found that students like to be taught to write narrative texts using series pictures. This is shown from the results of the questionnaire, students showed good responses and students answered that by using this series of pictures writing narrative texts became more fun, easier, helpful in stringing words, and easy to understand. It can be concluded that the student's response to the use of picture series in improving the ability to write narrative text is good and positive.